Health Benefits of Probiotics: A Review. (2nd January 2013) - Kechagia, Maria; Basoulis, Dimitrios; Konstantopoulou, Stavroula; Dimitriadi, Dimitra; Gyftopoulou, Konstantina; Skarmoutsou, Nikoletta; Fakiri, Eleni Maria
Abstract : Probiotic bacteria have become increasingly popular during the last two decades as a result of the continuously expanding scientific evidence pointing to their beneficial effects on human health. As a result they have been applied as various products with the food industry having been very active in studying and promoting them. Within this market the probiotics have been incorporated in various products, mainly fermented dairy foods. In light of this ongoing trend and despite the strong scientific evidence associating these microorganisms to various health benefits, further research is needed in order to establish them and evaluate their safety as well as their nutritional aspects. The purpose of this paper is to review the current documentation on the concept and the possible beneficial properties of probiotic bacteria in the literature, focusing on those available in food.